CONTRIBUTION OF VILLAGE FARMERS IN SUPPORTING GOLDEN INDONESIA 2045 - Titin; Safruddin; Magdalena Sunarty Pareira; Didi Tarmidi; Slamet Pamuji (Adisam Publisher, 2024)
The role of farmers, especially those in villages, has an important role in the running of the national economy, but there is a lack of supporting alternatives for the sustainability of the agricultural sector in rural areas. The future of Indonesian agriculture is threatened by the decreasing interest of the younger generation in engaging in agriculture, especially food farming. The Golden Indonesia 2045 generation farmers play an important role in realizing sustainable food through competencies that are in line with the Industrial Revolution 4.0. Indonesia has 84.4 million people who are young people under the age of 18 years. Of that number, 20- 30 percent are expected to become Indonesian Golden Generation farmers in 2045 or when the 100th anniversary of the independence of the Republic of Indonesia will be under 40 years old who can create food self-sufficiency for Indonesia. This research is qualitative research with a descriptive approach. Researchers use research data in the form of secondary data obtained from a number of credible sources such as scientific articles, books and a number of other sources that are credible and commonly used in research. These data were analyzed using analytical tools with stages of data collection, data selection, data reduction and drawing conclusions.